Adequate opportunity and the Principle of Inviolability of the Right to Defense (Legal journal - Research in Legal and Social Sciences, 2024)
Within the series of constitutional principles and guarantees that regulate the criminal process, the so-called adequate opportunity contained in art. 350 of the criminal procedural order is of special interest, since it constitutes the materialization and effective exercise of the principle of inviolability of the right to defense, which in turn responds to the principle of defense in trial contained in the National Constitution. For this reason, it is proposed to outline the circumstances that must be considered to demonstrate that the accused has been given the opportunity to give an interrogatory statement in the preparatory stage and that it was sufficient in accordance with the provisions of art. 350 of the Criminal Procedure Code. For this purpose, the method used was a qualitative approach with a non-experimental design, of a dogmatic-documentary type with a descriptive scope of the judicial precedents and the analysis of the procedural and constitutional norm in order to obtain the standardization of the assumptions that must be present in this guarantee. The research developed exposes the neuralgic position of this appropriate and timely access; referring to the time and way in which the accused can have access to evidence that really allows him to exercise his material defense within the design of the criminal process and its implementation in terms of compliance with the principle of inviolability of the right to defense in trial.
Keywords: adequate opportunity; constitutional guarantees; inviolability of the right to defense; right to be heard